Review Article about Stages of Breast Cancer - Ehmeid, Ali Radwan Awad; Abraham, Yusser Jameel Kamel; Muhammad, Hadeel Basem Hussein; Shawi , Hassan Eiqal Ismail (American Journal of Biology and Natural Sciences, 2024)
Breast cancer stages are classified using Roman numerals ranging from 0 to IV, with stage 0 indicating cancer that is noninvasive or confined to the milk ducts. Higher numbers indicate more extensive cancer. By stage IV breast cancer, also called metastatic breast cancer, the cancer has spread to other parts of the body. The cancer staging system continues to evolve and become more complex as doctors improve cancer diagnosis and treatment.